The Influence of Educational Background, Training Programs, and Career Development on Employee Performance at the Personnel and Human Resources Development Agency (BKPSDM) of Malang City - Nindi Hide; Retno Ayu Dewi Novitawati; Yuni Setyawati (International Journal of Management and Business, 2026)
The purpose of this study was to determine the partial and simultaneous effects of career development, training programs, and educational background on employee performance at the “Personnel and Human Resource Development Agency (BKPSDM) of Malang City.” The quantitative approach is the research methodology used. A questionnaire made with a Likert scale serves as a data collection tool. The research sample consisted of forty-five respondents, all of whom worked at BKPSDM Malang City. Multiple linear regression techniques were used to analyze the data. The findings of the study indicate that although career advancement has no significant impact on employee performance, training programs and educational background have a good and significant impact. Employee performance is significantly influenced by training programs, career growth, and educational background simultaneously. These findings indicate that although career development still needs further assessment to truly contribute to improved performance, proper education and training can improve employee work productivity.